On convergence of rotational hardening with bounds in clay plasticity. Issue 3 (24th June 2019) - Dafalias, Y. F.; Taiebat, M.; Rollo, F.; Amoros, A.
Abstract : The convergence of the rotational hardening variable α used in anisotropic models of clay plasticity, with a constitutively defined attractor/bound αb ( η ) function of the stress ratio η, under fixed η loading, is analytically investigated. It is rigorously shown that depending on various parameters of the rate equation of evolution of α such convergence may or may not occur, despite the apparent necessity of convergence stemming from the form of the evolution equation of α .